KLASIFIKASI KOMUNITAS BURUNG DICAGAR ALAM GUNUNG TINOMBALA KECAMATAN MEPANGA KABUPATEN PARIGI MOUTONG - Miranda, Tyas; M., Sri Ningsih; Ihsan, Moh. (Warta Rimba, 2014)
Few studies have explicitly determine classification on bird community in nature reserve areas in Central Sulawesi. Here in, we reported upon the results of bird community classification, species composition and similarity index in Tinombala Nature Reserve area, Mepanga district, Parigi Moutong, Central Sulawesi.The study was conducted on may through june 2013.The birds composition was recorded by using Index Point of Abundance (IPA-count) method. Studies were conducted in four bird habitat types, i.e; along river (watershed area) Â± 822m above sea level(LS: 00Âº 35 38,1"- BT: 120Âº 40 22,3"), garden Â± 785m (LS: 00Âº 35 2,1"- BT: 120Âº 41 32,8"), secondary forest Â± 1045m (LS: 00Âº 35 14,1 "- BT: 120Âº 40 24,4"), and primary forest Â± 1104m dpl (LS: 00 Âº 37â 51,0" - BT: 120Âº 40 4,5"). The result showed that the bird species found at four habitat types were as many as 23 families with 41 species of birds and total number of bird was 210 individual bird. Close bird habitat classification was founded between habitat watershed area and primary forest with value 14,24. The highest similarity index was achieved by Mullerpicus fulvus, Macropygia amboinensis, Hypothimis azurea, Oriolus chinensis, and Dicaeum celebicum. Keywords: Classification, Bird Community, Tinombala Nature Reserve.